The Earth in the Solar System, a website for teaching Physical Geography - Bravo Montano , Norma Yadira (Revista Minerva, 2021)
The presence of Information and Communication Technologies have produced profound changes in the teaching-learning media by incorporating some new ones and changing many of the methods and techniques for the realization of the traditional ones. In this sense, one of the most relevant and powerful means when it comes to making information available to the student is constituted by Web sites, a means that has experienced great expansion over the last few years. Today it is not enough to perfect the programs, teaching materials among others; It is also necessary to incorporate into the teaching-learning process, in a harmonious and rational way, teaching-learning means that allow an in-depth analysis of knowledge, which are not limited only to theory, but transcend practice. web "The Earth in the Solar System" related to the contents of the Universe from the facilities provided by its implementation of a teaching-learning medium that, accompanied by methodological proposals for this content, favors the acquisition of the contents of the Topic. The possibilities that technological resources contribute to the teaching-learning process of Geography affect its activation, since it allows students to participate in the search for knowledge, which together with the attraction of technology itself, allows increasing motivation to this science.
Keywords: Technologies; website; teaching-learning medium